Brazilian green propolis improves gut microbiota dysbiosis and protects against sarcopenic obesity. Issue 6 (26th September 2022) - Okamura, Takuro; Hamaguchi, Masahide; Bamba, Ryo; Nakajima, Hanako; Yoshimura, Yuta; Kimura, Tomonori; Hashimoto, Yoshitaka; Majima, Saori; Senmaru, Takafumi; Ushigome, Emi; Nakanishi, Naoko; Asano, Mai; et al.
Abstract: Introduction: Brazilian green propolis is an important honeybee product that is considered beneficial for health. Here, we examined the therapeutic potential of dietary supplementation with propolis against sarcopenic obesity using Db/Db mice. Methods: Db/m mice fed a normal diet alone and Db/Db mice fed normal diet alone, or supplemented with different amounts of propolis (0.08, 0.4 and 2%), were examined for effects on sarcopenic obesity. Results: Propolis improved the glucose tolerance ( P < 0.001), increased the grip strength ( P < 0.001) and the weight of soleus ( P = 0.006) and plantaris muscles ( P = 0.008). Moreover, propolis improved the non‐alcoholic fatty liver disease activity score ( P < 0.001) and decreased the expression of genes related to inflammation, liver fibrosis and fatty acid metabolism. Propolis decreased the accumulation of saturated fatty acids in the liver and increased their excretion in faeces. With regard to the innate immunity, propolis decreased the ratio of M1 macrophages ( P = 0.008) and Type 1 and 3 innate lymphoid cells to CD45‐positive cells ( P < 0.001) and increased the ratio of M2 macrophages ( P = 0.002) and ILC2s ( P = 0.007) in the liver. Additionally, propolis decreased the expression of genes related to muscle atrophy and inflammation and the concentration of saturated fatty acids in the soleus muscle. 16S rRNA phylogenetic sequencing revealed that propolis increased the Bacteroidetes/Firmicutes ratio, and the abundance of Butyricicoccus and Acetivibrio genera. Gut microbiota related to the pentose phosphatase pathway and glycerolipid metabolism was more prevalent after the administration of propolis. Conclusions: This is the first study to demonstrate that propolis can improve sarcopenic obesity by improving dysbiosis due to overeating and provides new insights into diet–microbiota interactions during sarcopenic obesity.